Oral health of Anganwadi children in Tumkur city: A field study - Mythri Halappa; J V Bharateesh; Herbert Kristen Liveiro; P Rameeza; Sameeha Mohammad Basheer; Linta Teresa James (Wolters Kluwer Medknow Publications, 2016)
Objective: In India, due to illiteracy and poor socioeconomic conditions, along with harmful oral habits, the prevalence of oro-dental diseases is widespread. Primary health care approach is the strategy to attain health for all. Hence, the objective was to assess oral health of Anganwadi children. Methodology: A descriptive cross-sectional study was designed to include 316 children from Anganwadi present in the vicinity of a field area of the dental institute, Tumkur. Results: The prevalence of dental caries was 41.77%, mean decayed, extracted, filled tooth being 2. Conclusion: The prevalence of dental caries in Anganwadi children was high indicating the need for both preventive and curative methods. The comprehensive treatment along with oral hygiene instructions was provided.